Polyomavirus BK Replication in De Novo Kidney Transplant Patients Receiving Tacrolimus or Cyclosporine: A Prospective, Randomized, Multicenter Study. Issue 1 (8th November 2012) - Hirsch, H. H.; Vincenti, F.; Friman, S.; Tuncer, M.; Citterio, F.; Wiecek, A.; Scheuermann, E. H.; Klinger, M.; Russ, G.; Pescovitz, M. D.; Prestele, H.
<x xml:space="preserve">Abstract</x> Polyomavirus BK (BKV)‐associated nephropathy causes premature kidney transplant (KT) failure. BKV viruria and viremia are biomarkers of disease progression, but associated risk factors are controversial. A total of 682 KT patients receiving basiliximab, mycophenolic acid (MPA), corticosteroids were randomized 1:1 to cyclosporine (CsA) or tacrolimus (Tac). Risk factors were analyzed in 629 (92.2%) patients having at least 2 BKV measurements until month 12 posttransplant. Univariate analysis associated CsA‐MPA with lower rates of viremia than Tac‐MPA at month 6 (10.6% vs. 16.3%, p = 0.048) and 12 (4.8% vs. 12.1%, p = 0.004) and lower plasma BKV loads at month 12 (3.9 vs. 5.1 log10 copies/mL; p = 0.028). In multivariate models, CsA‐MPA remained associated with less viremia than Tac‐MPA at month 6 (OR 0.60; 95% CI 0.36–0.99) and month 12 (OR 0.33; 95% CI 0.16–0.68). Viremia at month 6 was also independently associated with higher steroid exposure until month 3 (OR 1.19 per 1 g), and with male gender (OR 2.49) and recipient age (OR 1.14 per 10 years) at month 12. The data suggest a dynamic risk factor evolution of BKV viremia consisting of higher corticosteroids until month 3, Tac‐MPA compared to CsA‐MPA at month 6 and Tac‐MPA, older age, male gender at month 12 posttransplant.